COMPARISON OF LEGAL PROTECTION FOR PATIENTS IN DIFFERENT COUNTRIES: A LITERATURE STUDY - Hotmaria Hertawaty Sijabat; Gunawan Widjaja (Jurnal Kesehatan, 2025)
This article examines the comparative legal protection for patients in different countries by conducting a comprehensive literature review. The analysis shows that there is great variation in the legal protection provided, influenced by each country's level of economic development, health system, and government policies. Developed countries generally have more comprehensive legal frameworks that protect patients' rights, including the right to medical information, informed consent, and effective grievance mechanisms. In developing countries, legal protection for patients is often weaker due to limited resources and infrastructure. This study recommends increased public awareness of patients' rights, training for medical personnel, and international co-operation to set global standards, in order to strengthen legal protection for patients globally.